Effect of etching time and light sources on the shear bond strength of metal brackets to ceramic cylinders - PIAIA,Magda Regina (2014)
OBJECTIVE: To evaluate the shear bond strength of brackets bonded to ceramic with Transbond XT resin, etching time intervals (1 and 2 minutes) and three Light sources (Xenon Plasma Arc, LED and Halogen Light ), with and without silane. METHODS: In total, 12 feldspathic ceramic cylinders (15 mm x 20 mm), etched with 10% hydrofluoric acid were used. For light activation, the brackets were divided according to the light source to be used (n-15): LED UltraLume 5 (L); Apollo 95E plasma arc (AP) and Halogen light XL 2500 (H). After 24 h the samples were submitted to shear bond strength testing at crosshead speed of 0.5 mm/minute. RESULTS: The data were submitted to the analysis of variance (ANOVA) and the Tukey test (5%). Bond Strength: UltraLume 5 (11.4 ± 3.56 MPa) was superior to XL 2500 (9.12 ± 2.83 MPa) and Plasma Arc (5.11 ± 2.93 MPa) (p<0.05). No difference was found between ceramic with silane (8.31 ± 4.17 MPa) and without silane (8.68 ± 3.86 MPa). Etching time of 2 minutes (9.13 ± 3.98 MPa) was superior to time of 1 minute (7.86 ± 3.96 MPa). CONCLUSION: The results showed that LED was shown to be more efficient for polymerizing the material for Transbond XT bonding. The use of silane did not influence the bond strength values. The acid etching time of 2 minutes was more effective than that of 1 minute.